2013
DOI: 10.4049/jimmunol.1202800
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte- and Macrophage-Targeted NADPH Oxidase Mediates Antifungal Host Defense and Regulation of Acute Inflammation in Mice

Abstract: Chronic granulomatous disease, an inherited disorder of the NADPH oxidase in which phagocytes are defective in the generation of superoxide anion and downstream reactive oxidant species, is characterized by severe bacterial and fungal infections and excessive inflammation. Although NADPH oxidase isoforms exist in several lineages, reactive oxidant generation is greatest in neutrophils, where NADPH oxidase has been deemed vital for pathogen killing. In contrast, the function and importance of NADPH oxidase in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…Mice deficient for Ncf1, encoding p47 phox which is one component of the assembled NADPH oxidase complex, were used as murine models of CGD [24]. Ncf1-deficient mice with transgenic rescue of Ncf1 under the human CD68 promoter, which gained the expression of NCF1 and functional NADPH oxidase activity specifically in monocytes/macrophages, demonstrated that spontaneous or induced bacterial/fungal infections and the production of inflammatory cytokines in response to β-glucan were reduced compared with mice globally deficient for Ncf1 [25][26][27]. Similarly, our results of the present patient suggest the specific contribution of monocyte/macrophage NADPH oxidase to antimicrobial host defense and to the downregulation of hyperinflammation which is often observed in an X-CGD patient with NADPH oxidase-incompetent phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient for Ncf1, encoding p47 phox which is one component of the assembled NADPH oxidase complex, were used as murine models of CGD [24]. Ncf1-deficient mice with transgenic rescue of Ncf1 under the human CD68 promoter, which gained the expression of NCF1 and functional NADPH oxidase activity specifically in monocytes/macrophages, demonstrated that spontaneous or induced bacterial/fungal infections and the production of inflammatory cytokines in response to β-glucan were reduced compared with mice globally deficient for Ncf1 [25][26][27]. Similarly, our results of the present patient suggest the specific contribution of monocyte/macrophage NADPH oxidase to antimicrobial host defense and to the downregulation of hyperinflammation which is often observed in an X-CGD patient with NADPH oxidase-incompetent phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered the systemic reservoir of myeloid precursors for renewal of tissue macrophages and dendritic cells. Monocytes play a key role during immune response as professional phagocytes 21, 22 , and producers of immune mediators 23, 24 . Indeed, reports show that monocytes are recruited at the site of infections as innate effectors of the inflammatory response to microbes, killing pathogens via phagocytosis, production of reactive oxygen intermediate (ROIs) 25 , reactive nitrogen intermediate (RNIs) 26, 27 , myeloperoxidase (MPO) 28, 29 , and producing inflammatory cytokines 30 that contribute to further amplifying the antimicrobial response 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ROS production is intimately linked with phagosomal pH. ROS and its toxic oxidant byproducts have long been recognized as crucial for phagosomal killing in neutrophils 4,11,12 , and have been shown to play critical roles in other phagocytes including macrophages, dendritic cells (DCs) and amoeba [13][14][15][16] . The NADPH oxidase is an electrogenic enzyme that releases H + in the cytosol as NADPH is consumed, and that requires the simultaneous transfer of H + through companion HVCN1 channels alongside the transported electrons into the phagosomal lumen, in order to alleviate the massive depolarization that would otherwise lead to self-inhibition of the enzyme [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%